Use of industrial ceramic sludge in brick production: Effect on aesthetic quality and physical properties. (15th October 2016) - Coletti, Chiara; Maritan, Lara; Cultrone, Giuseppe; Mazzoli, Claudio
Highlights: Re-using sludge from the ceramic industry as an alternative eco-friendly additive. Aesthetic quality and physical properties of traditional bricks and new mix design. Economic and ecologic ways of developing bricks from recycled waste. Abstract: Most brick companies nowadays focus their research on the recycling of waste, in order to be able to market new types of bricks. In this work, we explored the possibility of using ceramic sludge in brick production, aiming to find an alternative eco-friendly additive to produce "eco-bricks" characterised by suitable mechanical and aesthetic properties and durability. For this purpose, two types of bricks produced by an Italian factory (SanMarco-Terreal) were compared with a newly designed brick obtained from the same starting clay, with the addition of ceramic sludge in place of the traditionally used siliceous sand. Bricks and raw materials were investigated with a multivariate approach, consisting in the mineralogical and chemical analysis, and the final products microstructurally investigated and their physical-mechanical properties determined. Results show that bricks produced with added ceramic sludge can substitute traditional bricks well, fulfilling aesthetic requirements and maintaining sufficient mechanical properties. However, one drawback was that these new materials did not respond to freeze-thaw cycles, highlighting their potential vulnerability in cold climates.